Vestibular Function Tests for Vestibular Migraine: Clinical Implication of Video Head Impulse and Caloric Tests - Kang, Woo Seok; Lee, Sang Hun; Yang, Chan Joo; Ahn, Joong Ho; Chung, Jong Woo; Park, Hong Ju (Frontiers in Neurology, 2016)
Vestibular migraine (VM) is one of the most common causes of episodic vertigo. We reviewed the results of multiple vestibular function tests in a cohort of VM patients who were diagnosed with VM according to the diagnostic criteria of the Barany Society and the International Headache Society and assessed the efficacy of each for predicting the prognosis in VM patients. A retrospective chart analysis was performed on 81 VM patients at a tertiary care center from June 2014 to July 2015. Patients were assessed by the video head impulse test (vHIT), caloric test, vestibular-evoked myogenic potentials (VEMP), and sensory organization test (SOT) at the initial visit and then evaluated for symptomatic improvement after 6 months. Complete response (CR) was defined as no need for continued medication, partial response (PR) as improved symptoms but need for continued medication, and no response (NR) as no symptomatic improvement and requiring increased dosage or change in medications. At the initial evaluation, 9 of 81 patients (11%) exhibited abnormal vHIT results, 14 of 73 (19%) exhibited abnormal caloric test results, 25 of 65 (38%) exhibited abnormal SOT results, 8 of 75 (11%) exhibited abnormal cervical VEMP results, and 20 of 75 (27%) exhibited abnormal ocular VEMP results. Six months later, 63 of 81 patients (78%) no longer required medication (CR), while 18 (22%) still required medication, including 7 PR and 11 NR patients. Abnormal vHIT gain and abnormal caloric results were significantly related to the necessity for continued medication at 6-month follow-up (OR = 5.67 and 4.36, respectively). Abnormal vHIT and caloric test results revealed semicircular canal dysfunction in VM patients and predicted prolonged preventive medication requirement. These results suggest that peripheral vestibular abnormalities are closely related to the development of vertigo in VM patients.